Enhancing the Survival of Ichneumonid Parasitoid Campoletis chlorideae (Hymenoptera: Ichneumonidae) by Utilizing Haserpin-e Protein to Effectively Manage Lepidopteran Pests - Liuming Huo; Xue Yao; Ningbo Zhang; Shengyi Wang; Sufen Bai; Yanmei Wang; Jizhen Wei; Shiheng An (Insects)
The ichneumonid parasitoid Campoletis chlorideae is an important natural enemy of lepidopteran pests in different agro-ecosystems, specifically targeting early larvae (second- and third-instar). Enhancing the survival of C. chlorideae, especially within hosts, remains a significant technical challenge for large-scale indoor reproduction. This study investigates the use of endogenous serpin-e protein, derived from the host Helicoverpa armigera (Haserpin-e), to improve the survival rate of C. chlorideae in indoor reproduction. The results demonstrated that Haserpin-e protein significantly enhanced cocoon production in C. chlorideae, with no observable adverse effects on the life history traits of both F0 and F1 generations of C. chlorideae. By investigating the mechanism underlying cocoon formation promotion, it was found that Haserpin-e protein reduced the encapsulation, inhibited melanization, as well as suppressed the expression of antimicrobial proteins (AMPs) in H. armigera. This study provides novel insights into improving the survival of C. chlorideae by inhibiting host immune responses through the application of its endogenous Haserpin-e protein during large-scale indoor reproduction efforts. Additionally, this research further elucidates the multifaceted functionality of Haserpin-e proteins by demonstrating their role in regulating innate immune processes in H. armigera, including negatively regulating encapsulation, melanization, and AMP expression.